The Influence of Internal Audit and Risk Control on Crisis Management in the Tourism Industry in Indonesia - Dewi, Irra Chrisyanti; Sudarmanto, Eko; Yulianti, Eka Budi; Legito, Legito; Susanto, Edy (The Es Accounting And Finance, 2024)
This research investigates the complex interactions between Internal Audit, Risk Control, and Crisis Management in the dynamic landscape of Indonesia's tourism industry. Using a quantitative approach, this study employed Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze survey data collected from stakeholders in the industry. Descriptive statistics showed positive perceptions of Internal Audit and Risk Control, with room for improvement in Crisis Management effectiveness. Measurement model assessment established reliability and construct validity, paving the way for robust structural model analysis. The results show that Internal Audit and Risk Control significantly and positively influence Crisis Management. Practical implications include customized strategies for optimal crisis resilience, while policy recommendations underscore the importance of a standardized framework. Despite its limitations, this study contributes valuable insights to the crisis resilience literature, offering a nuanced understanding of the dynamics of Indonesia's tourism sector.